Late-Stage Trifluoromethylation - Verhoog, S (2016)
This thesis is concerned with the development of methodology for late-stage trifluoromethylation of complex molecules. Chapter 1 introduces the concept of late-stage trifluoromethylations and details the effect that substitution of a CF3 group can have on the properties of organic molecules. Methods for generating reactive trifluoromethylating intermediates for use in allylic and aliphatic trifluoromethylation are also discussed. Chapter 2 examines the photoredox catalysis as a mechanistic manifold for the trifluoromethylation of allylsilanes for the synthesis of branched allylic trifluoromethylated compounds. The stereogenic trifluoromethylation of enantio-enriched allylsilanes through chirality transfer is explored, and mechanistic experiments are performed to investigate the formation of the CF3 radical intermediate. Chapter 3 details the development of hydrotrifluoromethylation of terminal alkenes for the synthesis of aliphatic trifluoromethylated compounds under mild conditions using photoredox catalysis. This methodology tolerates a wide range of functional groups and is applicable to the late-stage trifluoromethylation of complex organic compounds. Chapter 4 explores the synthesis and isolation of 18F-labelled aryl -SCF3, -OCF3 and - OCF2H compounds from high specific activity [18F]fluoride, using Ag(I) mediated halogen exchange as a mode of activation. This methodology can be used for the synthesis and isolation of 18F labelled radiotracers containing new functional groups that have interesting biological and pharmacological properties. Chapter 5 contains full experimental procedures and characterisation data for compounds synthesised in chapters 2, 3 and 4.